Pengembangan Panduan Bimbingan Dan Konseling Untuk Mengembangkan Kecerdasan Sosial Siswa - Maryam Rahim; Meiske Puluhulawa (Program Studi bimbingan Konseling PPs UNM Makassar, 2019)
This study aims to produce a guide to improve teacher competency in guidance and counseling in developing social intelligence of seventh grade junior high school students, which consists of: (1) service syllabus and plan for implementing guidance and counseling services, (2) teacher guidance, (3) material services, and (4) evaluation guidelines. The procedure for developing a 5-step guide is: (1) analyzing the product to be developed, (2) developing the initial product, (3) expert validation and revision, (4) small-scale field testing and product revision, and (5) trial large scale field and final product. Based on the results of expert validation data analysis, small group test data and large group tests, as well as product revisions based on the results of data analysis that has been obtained, guidance and counseling service guides can be produced that have criteria for developing social intelligence of seventh grade junior high school students. This guide consists of (1) service syllabus and plan for implementing guidance and counseling services, (2) teacher guidance, (3) service material, and (4) evaluation guidelines. It is expected that the guidance and counseling teachers can use this guide in carrying out guidance and counseling services for the development of students' social intelligence, especially seventh grade junior high school students.